Monitoring radionuclides in subsurface drinking water sources near unconventional drilling operations: a pilot study. (April 2015) - Nelson, Andrew W.; Knight, Andrew W.; Eitrheim, Eric S.; Schultz, Michael K.
Abstract: Unconventional drilling (the combination of hydraulic fracturing and horizontal drilling) to extract oil and natural gas is expanding rapidly around the world. The rate of expansion challenges scientists and regulators to assess the risks of the new technologies on drinking water resources. One concern is the potential for subsurface drinking water resource contamination by naturally occurring radioactive materials co-extracted during unconventional drilling activities. Given the rate of expansion, opportunities to test drinking water resources in the pre- and post-fracturing setting are rare. This pilot study investigated the levels of natural uranium, lead-210, and polonium-210 in private drinking wells within 2000 m of a large-volume hydraulic fracturing operation – before and approximately one-year following the fracturing activities. Observed radionuclide concentrations in well waters tested did not exceed maximum contaminant levels recommended by state and federal agencies. No statistically-significant differences in radionuclide concentrations were observed in well-water samples collected before and after the hydraulic fracturing activities. Expanded monitoring of private drinking wells before and after hydraulic fracturing activities is needed to develop understanding of the potential for drinking water resource contamination from unconventional drilling and gas extraction activities. Graphical abstract: Highlights: Natural radionuclides in ground water near unconventional drilling operations were investigated. Natural uranium ( nat U), lead-210 ( 210 Pb), and polonium-210 ( 210 Po) levels are described. No statistically significant increases in natural radioactivity post-drilling were observed.